How sex works : why we look, smell, taste, feel, and act the way we do - Moalem, Sharon (HarperCollins, 2009)
Neurogeneticist Moalem takes us on a trip from prehistory to the forefront of cutting-edge medical research, and through a bedroom or two, to tell the story of how human sexuality has developed over time. This book challenges common perceptions about our bodies and presents astonishing discoveries from the frontiers of science as it traces the transformation of sex across species and through time to its current role in human societies. Find out the answers to such provocative questions as: Can the birth control pill influence the type of men women are attracted to? What do men and honeybees have in common when it comes to sex? When are women most likely to cheat? From the composition and function of human sex organs to the fascinating biochemistry behind sexual attraction, How Sex Works presents captivating new ideas and surprising answers to questions about contraception, fertility, circumcision, menopause, STDs, homosexuality, orgasms, and more.--From publisher description.